2022
DOI: 10.3389/fmars.2022.896157
|View full text |Cite
|
Sign up to set email alerts
|

A Regional View of the Response to Climate Change: A Meta-Analysis of European Benthic Organisms’ Responses

Abstract: Climate change is impacting organisms in every region of the world ocean by acting though on individuals in response to their local environments. Given projected future risks derived from these changes, it is becoming increasingly important to understand regional signals of how organisms respond to facilitate their governance and protection. Benthic organisms structure ecological compositions and ecosystem dynamics, therefore not only providing insights into their own response to climate change but also how ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 104 publications
0
10
0
Order By: Relevance
“…We preformed meta-analysis on the impacts of climate stressors on the growth of Bivalvia at whole-class and family levels following methods described in Hoppit and Schmidt (2022). Stressors identified from the included Figs 3-5; Table 2). Stressor effects could be synergistic (additive) or antagonistic (dampening) (sensu Harvey et al, 2013), or dominated by one stressor (unaffected by changes in another stressor).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We preformed meta-analysis on the impacts of climate stressors on the growth of Bivalvia at whole-class and family levels following methods described in Hoppit and Schmidt (2022). Stressors identified from the included Figs 3-5; Table 2). Stressor effects could be synergistic (additive) or antagonistic (dampening) (sensu Harvey et al, 2013), or dominated by one stressor (unaffected by changes in another stressor).…”
Section: Discussionmentioning
confidence: 99%
“…Up to 40% of the world's population lives within 200 km of the coastline (Neumann et al, 2015), and an estimated 775 million people globally have high dependence on these systems and their services (Selig et al, 2019). Costal ecosystems are estimated to contribute more than 60% of the total economic value of the biosphere (Martínez et al, 2007) but organisms adapted to live in these systems are predicted to suffer large alterations in their population fitness in response to future climate change (Kroeker et al, 2013;Sampaio et al, 2021;Hoppit and Schmidt, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated the effects of climate change on the morphology and chemical composition of carbonate skeletons [2][3][4][5], which influence their mechanical properties. For example, changes to the cellular structure within coralline algae can change internal stress distributions [6], while increased incorporation of Mg into the crystal lattice increases the solubility and hardness of the carbonate material as demonstrated in sea urchin teeth and corallines [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, such approaches cannot reflect the integration of diverse environmental factors nor the long-term sustainability of river ecosystems [22]. In contrast, bioindicators are used to define the health of an ecosystem; they not only provide insights into their own response to environmental disturbance but also are capable of predicting how ecosystems might respond to future conditions [23,24]. Bioindicators are, therefore, among the proposed tools for monitoring ecological integrity and environmental pollution, with high applicability to water quality assessment [23,25].…”
Section: Introductionmentioning
confidence: 99%